PERSEPSI MAHASISWA AKUNTANSI DALAM PEMILIHAN KARIR MENJADI AKUNTAN PUBLIK : BEBERAPA FAKTOR PENENTU - Tian Ariyanto; Maria Goreti Kentris Indarti (Faculty of Economics and Business, Universitas Warmadewa, 2023)
This study aims to empirically examine the considerations of the labor market, social values, and work environment on the perceptions of accounting students in choosing a career to become a public accountant by using a questionnaire distributed to respondents. The population used was students of the S-1 accounting study program at Stikubank University (UNISBANK) Semarang and Dian Nuswantoro University. In selecting the sample using purposive sampling technique with predetermined criteria. To test this study, researchers used a sample of 92 consisting of 20 male and 72 female. To obtain the value that supports this study using multiple linear analysis methods assisted by applicationsSPSS. Based on the results of the analysis that has been carried out, it shows that considerations of the labor market have a positive effect on the perceptions of accounting students in choosing a career to become a public accountant, social values have a positive effect on the perceptions of accounting students in choosing a career to become a public accountant, and work environment have a positive effect on the perceptions of accounting students in choosing a career to become a public accountant